2017
DOI: 10.1007/s00281-017-0658-5
|View full text |Cite
|
Sign up to set email alerts
|

Recipe for IBD: can we use food to control inflammatory bowel disease?

Abstract: The mucosal immune system and the microbiota in the intestinal tract have recently been shown to play a key role in the pathogenesis of inflammatory bowel disease (IBD). Both of these can be influenced by food. Thus, we propose dietary intervention as a therapeutic option for IBD. In this review, we discuss the interaction of the intestinal mucosal immune system and the intestinal microbiota in the context of IBD. In addition, we discuss the impact of food components on immune responses in IBD. Finally, we add… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 149 publications
0
25
1
1
Order By: Relevance
“…Food components can affect incidence of IBD and its development at least through modulation of intestinal microbiota, intestinal immune system and inflammation [6]. Studies investigating dietary determinants in the onset of IBD are increasing and some of these suggest meat [7], dairy [8], fiber [9], and vitamin D [10] may influence the risk of developing IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Food components can affect incidence of IBD and its development at least through modulation of intestinal microbiota, intestinal immune system and inflammation [6]. Studies investigating dietary determinants in the onset of IBD are increasing and some of these suggest meat [7], dairy [8], fiber [9], and vitamin D [10] may influence the risk of developing IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Results from a recent publication showed that a pro-inflammatory diet is associated with greater proinflammatory gene expression among non-obese individuals ( 38 ). Considering the role of inflammatory mediators including cytokines in the regulation of intestinal immune responses and intestinal mucosal barrier homeostasis ( 39 ), cytokines play a critical role in causing the chronic inflammatory condition in IBD ( 40 ). Therefore, consumption of a pro-inflammatory diet can contribute to UC pathogenesis through increasing serum levels of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities of the gut microbiome are common in different intestinal conditions, including IBD. In fact, an altered microbiota has been reported in IBD ( 10 , 39 ). Diet can affect the gut microbiota ( 42 , 43 ), as a recent publication revealed a correlation between intakes of energy and micronutrients such as vitamin A, vitamin D and, vitamin C, all contributed to IPD score, with fecal and mucosal communities in UC patients ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further results indicated that biochemical inhibition of QseC can reduce intestinal inflammation in a variety of preclinical IBD models, and provides a new approach for the treatment of colitis (149). Additionally, dietary interventions that modulate the interaction between the immune system and microbiota can also be an option for the treatment of IBD (150).…”
Section: Management Of Ibd: Targeting Stressmentioning
confidence: 99%